Rotation construction of heavy swivel arch bridge for high-speed railway. (August 2020) - Feng, Yu; Qi, Jianan; Wang, Jingquan; Zhang, Wenxue; Zhang, Qifeng
Abstract: Superstructure rotation method (SRM) can optimize bridge construction in terms of reducing impacts on traffic, safety and overall budget. This paper focus on the key scientific problems of the swivel arch bridge, and takes the world's largest high-speed railway swivel arch bridge on soft soil foundation over Hu-Hang highway as the engineering background. Construction technologies of this project including the installation process, design of the traction system and the precision control method are introduced. Optimum design method of tension force of the tie bars which considering 7 different load conditions during the construction process is proposed. As the key element of the construction of swivel arch bridge, a complete design process of the spherical hinge is present in detail. Exact analytical solution to determine the relationship of radial stress and upper load, which based on the solution of concentrated force acting on the half-plane body in the elastic mechanics, has been firstly put forward and compared with the simplified method recommended by codes. Meanwhile, reasonable ranges of geometric and material parameters have been given and elaborate design flows of the spherical hinge have been presented. Besides, overturning resistance checking design of the spherical hinge during the construction process have been presented also, which are particularly instructive for engineers and designers.